The effect of the ionosphere on astronomical observations below 100 MHz - De Gasperin, F.; Mevius, M.; Intema, Hubertus (2017)
© 2017 URSI. We derive the expected systematic error induced by the ionosphere on radio astronomical observations at low frequencies. We compare our predictions with data from the Low Frequency Array (LOFAR). We show that the systematic errors on the phases of the instrument can be described as a sum of four effects (clock, ionosphere 1st, 2nd, and 3rd order). We show that the ionosphere corrupts also the recorded data amplitude through scintillations. Finally, we report values of the ionosphere structure function in line with the literature.